2020
DOI: 10.1186/s13568-020-01045-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of metal-curcumin complexes on quorum sensing related virulence factors of Pseudomonas aeruginosa PAO1

Abstract: The use of metal complexes to reduce or inhibit virulence factors of Pseudomonas aeruginosa is a promising strategy for the management and control of infections caused by this multidrug-resistant pathogen. The present study aimed to investigate the anti-quorum sensing activity of sub-minimum inhibitory concentrations (sub-MIC) of copper(II) sulfate pentahydrate-curcumin complex (Cu-CUR), iron(III) nitrate nonahydrate -curcumin complex (Fe-CUR), zinc(II) chloride-curcumin complex (Zn-CUR) and free curcumin (fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…P. aeruginosa possesses almost all of the known antimicrobial resistance mechanisms which is why empirical antibiotic treatments are often ineffective [ 16 ]. As a consequence, finding novel alternative therapeutic approaches is a necessity, targeting the bacterial social behaviors involved in their pathogenesis is one of these promising approaches [ 3 , 39 ]. Targeting the bacterial cell-to-cell communication quorum sensing system (QS) has several merits, particularly it avoids direct any effect on bacterial growth, decreasing the emergence of bacterial resistance [ 3 , 20 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa possesses almost all of the known antimicrobial resistance mechanisms which is why empirical antibiotic treatments are often ineffective [ 16 ]. As a consequence, finding novel alternative therapeutic approaches is a necessity, targeting the bacterial social behaviors involved in their pathogenesis is one of these promising approaches [ 3 , 39 ]. Targeting the bacterial cell-to-cell communication quorum sensing system (QS) has several merits, particularly it avoids direct any effect on bacterial growth, decreasing the emergence of bacterial resistance [ 3 , 20 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This complex inhibited Gram (+) bacteria S. aureus and Gram (−) E. coli culture-associated biofilms, which was found to be positively correlated with the inhibition of bacterial alkaline phosphatase activity as shown by in silico studies [35]. Another study showed that a Cu 2+ -curcumin complex at a concentration of 1/4 MIC on P. aeruginosa highly inhibited biofilm formation, swarming and twitching motilities, and alginate and pyocyanin production, thus indicating its efficacy for the therapy and management of P. aeruginosa infections [34]. Curcumin-ruthenium complex exhibited strong antibiofilm activity compared to some FDA approved drugs [31].…”
Section: Antimicrobialmentioning
confidence: 84%
“…Another study showed that Cu 2+ -curcumin complexes showed higher growth inhibition of P. aeruginosa compared to free curcumin, as the minimum inhibitory concentration (MIC) of Cu 2+ -curcumin complexes and free curcumin was 62.5 and 125 µg/mL, respectively. Moreover, Cu 2+ -curcumin complexes (62.5 µg/mL) reduced bacterial cell growth [34].…”
Section: Antimicrobialmentioning
confidence: 96%
See 1 more Smart Citation
“…The complex [Cu(cur) 2 ] ( 60 ) (cur: curcumin) inhibited biofilm formation in the case of S. aureus and significantly repressed the expression of lasI and lasR genes, demonstrating its QS inhibitory effect [ 136 ].…”
Section: Complexes With Antibiofilm Activitymentioning
confidence: 99%